Factors Affecting the Occurrence of Hypertension in Pregnant Women - Muhamad Nor Mudhofar; Grace Carool Sipasulta; Jenti Sitorus (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Hypertension in pregnant women is one of the leading causes of maternal and perinatal morbidity and mortality. Identification of factors that contribute to the incidence of hypertension is essential to prevent further complications. Purpose: This study aims to analyze the factors that influence the occurrence of hypertension in pregnant women. Methods: This study used a quantitative analytic design with a cross-sectional approach. The samples used in this study were 109 pregnant women who visited the Ambacang Health Center at the time of the study. Data were collected through questionnaires and medical examinations, then analyzed using the chi-square test and multivariate logistic regression to determine the dominant factor. Results: The results showed that5 there was a significant relationship between age (>35 years) (p=0.003), BMI (p=0.001), family history of hypertension (p=0.005), and low ANC compliance (p=0.002) with the incidence of hypertension in pregnant women. The dominant factor was body mass index with OR=3.8 (95% CI: 1.9-7.6). Implications: The results of this study can be the basis for health workers in developing prevention programs and early detection of hypertension in pregnancy, as well as encouraging pregnant women to routinely conduct antenatal examinations. Conclusion: Several factors such as age, BMI, family history, and ANC compliance affect the occurrence of hypertension in pregnant women. Promotive and preventive interventions need to be improved, especially in monitoring nutritional status and adherence to antenatal care visits.